Use of clobetasol in lacquer for plaque psoriasis treatment - Suze Aparecida da Silva; Renata Ferreira Magalhães; Rafael Augusto Tamasauskas Torres; Raquel Diana de Oliveira; Paulo Eduardo Neves Ferreira Velho (Sociedade Brasileira de Dermatologia, 2016)
Abstract Clobetasol benefits to control psoriasis lesions are well defined, but there were not studies about its action when used in lacquer vehicle to control skin lesions. A double-blind study was conducted with 40 patients that utilized clobetasol 0.05% in one hemibody and just the vehicle in the other hemibody. Twenty of them used petrolatum as vehicle and the others used lacquer. An assessment was conducted using the clinical index PASI and a quality of life questionnaire (Dermatological Life Quality Index). There was no statistical difference between groups. There was a trend of favorable response particularly in the hemibody treated with clobetasol.